Parents’ perception of health education practices in Neonatal Unit - Souto, Nisa; Curado, Maria Alice dos Santos; Henriques, Maria Adriana (Universidade Federal do Rio de Janeiro, 2022)
Objective: to analyze parents’ perception of health education practices developed by nurses in a Neonatal Unit that facilitated the acquisition of parenting skills for an informed decision-making. Method: this is an exploratory, descriptive and qualitative study. We included 13 parents with children hospitalized for the first time in a Portuguese Neonatal Unit. Data were collected between February and August 2020, through focus groups, processed in the software Interface de R pour Multidimensionnelles de Textes et de Questionneires, through Descending Hierarchical Classification and Similitude Analysis. Results: four classes emerged from the Descending Hierarchical Classification: “Information needs”; “Information gaps”; “Availability to inform”; “Facilitating health education practices”. Conclusion and implications for practice: parents considered digital technology combined with nurses’ availability to inform and explain, as well as provide an empathetic and informal environment as facilitating practices for health education. These results can support health education nursing interventions for parents at the Neonatal Units using digital technology.
Keywords: Neonatologia; Enfermagem; Pais; Educação em Saúde; Literacia em Saúde